In children with foot and ankle injuries, does hopping count as non weight-bearing?. (24th May 2012) - Newton, T
Abstract : A pilot study of children attending an Emergency Department with foot or ankle injuries, hopping at presentation. Aims: In children presenting with foot and ankle injuries, an inability to weight bear is an indication for x-ray even in the absence of other signs of bony injury. Hopping is a vigorous action, quite different to the minimal movement that children with bony injuries adopt. We propose that hopping alone, with no other clinical features of a fracture, will not be associated with bony injury on x-ray; in essence that hopping and non weight bearing are not the same entity. Methods: Over a 2-year period, data was collected from children attending the department with foot and ankle injuries who hopped at presentation. The details recorded included the mechanism of injury, clinical findings, x-ray results and whether the children walked or hopped on discharge. All patients whose data was included in the study had x-rays either reported by the radiology department or by an Emergency Medicine Consultant. Results: A total of 66 proformas were completed but 18 were not included in the analysis as they had significant data missing (no x-ray report, no confirmation that they hopped into the department). From the remaining 48 patients, the following results were obtained: 9 patients had fractures on x-ray and in all cases these correlated with clinical findings. The remaining 39 patients (81.25%) had no bony injury on x-ray. 26 of these 39 did have other clinical signs that would have merited x-ray. The remaining 13 children (27% of the total) had no abnormal findings on examination. All of the children with no bony injury walked from the department on discharge. A Fisher's one-tailed test showed these results to be significant (p<0.05) Conclusion: This pilot study shows promising results but a larger study is required. If the results are replicated in a larger study, hopping could be distinguished from non weight bearing and, in children with injuries presenting with hopping alone and no other features to suggest bony injury, x-ray be avoided.